Digital signal processing a computer-based approach - Mitra, Sanjit Kumar (McGraw-Hill, 2011)
Based on Sanjit Mitra's extensive teaching and research experience, Digital Signal Processing, A Computer Based Approach, fourth edition, is written with the reader in mind. A key feature of this book is the extensive use of MATLAB-based examples that illustrate the program's powerful capability to solve signal processing problems. The book is intended for a course on digital signal processing for seniors or first-year graduate students. This highly popular book introduces the tools used in the analysis and design of discrete-time systems for signal processing. A number of changes have been made to the book's content, based on reviewer and student comments.